Printing noble metal alloy films with compositional gradient. (June 2022) - Chen, Jiahao; Saeidi-Javash, Mortaza; Palei, Milan; Zeng, Minxiang; Du, Yipu; Mondal, Kunal; McMurtrey, Michael D.; Hoffman, Anthony J.; Zhang, Yanliang
Abstract: Additive manufacturing has offered great promise in fabricating materials and devices with complex structures and unique properties. In addition to fabricating complex structures, additive manufacturing also allows for local changes to material compositions and structure, ideal for combinatorial material investigations. However, the on-demand control of compositional distributions in low dimensional materials remains challenging. In this work, we demonstrate a combinatorial aerosol jet printing technique to create noble metal films with gradient compositions. Nanoparticle sizes and ink chemistry are critical for aerosol jet printing and sintering process in order to achieve defect free thin films. Ruthenium (Ru) and platinum (Pt) nanoparticles with size <5 nm were synthesized and formulated into printable inks. After thermal sintering at temperature as low as 400 °C, printed nanoparticles formed highly reflective films free from microstructural defect. Alloy films of gradient compositions were realized via in-situ mixing Ru and Pt ink streams and varying the mixing ratio during the printing process. This combinatorial printing method provides great potential to rapidly transform nanoparticle inks into new materials compositions and structures unobtainable via conventional methods. Graphical abstract: Image, graphical abstract